Efluxo de metano relacionado com ácidos orgânicos no solo e carbono de exsudados radiculares no cultivo do arroz irrigado - Moscôso, Janielly Silva Costa (2018)
In worldwide greenhouse gases generation (GHGs) agriculture is one of the principal activities. In Brazil, as a reflection of the importance agriculture in economy, it is estimated that 75% of emissions of carbon dioxide (CO2), 94% of nitrous oxide (N2O) and 91% of methane (CH4) are contributed by agricultural activities. One of the agricultural activities that gets more attention in the emission of GHGs is irrigated rice cultivation, mainly in CH4 emission. In irrigated rice fields CH4 emission is characterized by two preferential peaks, one at the beginning of the crop, by the degradation of short chain organic acids present in soil and another in plant reproductive period, related to total organic carbon (TOC) exuded from its roots as a consequence of an intense photosynthetic activity. By understanding these two peaks of CH4 emission in irrigated rice can be a basis for its possible mitigation. The objective of this study was to evaluate the intervention mechanism of organic acids in the dynamics and potential emission of CH4 and to evaluate the contribution of TOC from root exudations of different cultivars of irrigated rice in CH4 emission, correlating the organic carbon derived from root exudation with CH4 efflux, physiological and agronomical aspects of cultivars. For this the present work was structured in two studies: 1st study was constructed as “dynamics and methane emission potential in flooded planosol under high doses of acetic, propionic and butyric acid” while the second study consisted of two experiments; Experiment I: “Total organic carbon exuded from rots of irrigated rice up to inflorescence” and Experiment II: “Methane emission from different cultivars of irrigated rice, physiological, agronomic and soil solution changes”. From the results obtained it was concluded that CH4 emission dynamics were altered with application of three organic acids of short chain in the soil, even using an equal dose of carbon. Faster and more intense CH4 emission was achieved with the application of acetic acid comparing to other two acids, when propionic acid was applied, there was a decrease in transformation efficiency to CH4 due to the acid stoichiometry itself and the temperature condition in which experiment was conducted. Regarding study II, it was concluded that irrigated rice cultivars showed differences in their TOC roots exotherm, with cultivars of precocious cycle having the lowest TOC values and this one obtained a higher correlation with the dry matter of the aerial part than with roots dry matter. Traditional cultivars reached an expressive CH4 emission value, even though they had a small TOC exudate content, as well as CH4 efflux dynamic was much more correlated with the organic carbon dissolved in soil solution than with TOC exotherm of roots. The agronomic and physiological parameters showed more correlation with TOC exotherm of roots of cultivars than with the emission of CH4.